2017
DOI: 10.1080/10402004.2017.1322735
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Characterisation of Graphene Oxide as Lubricant Additive on Hypereutectic Al-25Si/Steel Tribopair

Abstract: The performance of a lubricant greatly depends on the additives it involves. However, recently used additives produce severe pollution when they are burned and exhausted. Therefore, it is necessary to develop a new generation of green additives. Graphene oxide (GO) is considered to be environmentally friendly. The scope of this study is to explore the fundamental tribological behavior of graphene, the first existing 2D material, and evaluate its performance as a lubricant additive. The friction and wear behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Graphene, as a sheet-like nano material, is easy to enter the friction region [38]. In addition, graphene sheets with weak van der waals force are easy to slide between each other [39,40]. So we speculate that the addition of graphene reduces the friction coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene, as a sheet-like nano material, is easy to enter the friction region [38]. In addition, graphene sheets with weak van der waals force are easy to slide between each other [39,40]. So we speculate that the addition of graphene reduces the friction coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The 2D peak is associated with dual phonon scatter suchlike of electron-electron or electron-hole or hole-hole set. Moreover, it indicated as an inference of the D peak, but it does not necessarily represent flaws in the lattice formation [22,30].…”
Section: Tribofilm Testingmentioning
confidence: 99%
“…The nanomixture additives associated with the sliding balls produced enriched tribolayer between the mating surfaces of AISI ball. The mixture enriched film played antiwear and friction reduction attributes as demonstrated by energy-dispersive x-ray spectroscopy and elements mapping and Raman spectroscopy [17,30], Figures 11, 12 respectively. The average improvement in specific wear rate was 39.47 % for (0.4 wt.% ZnO + 0.2 wt.% graphene) nanolubricant compared with base lubricant due to the anti-wear mechanism of nano (zinc oxide and graphene) particles [12,31].…”
Section: Specific Wear Ratementioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30] They are used as additives in certain liquid lubricants to improve the antifriction and anti-wear properties. [31][32][33][34][35][36] Inspired by such established functionality of graphene, researchers have attempted to add it to grease. [37][38][39] Their results showed that graphene not only greatly reduces the friction coefficient but also minimises the wear spot diameter.…”
Section: Introductionmentioning
confidence: 99%